An Evaluation of the Quality of HCR-20 Risk Formulations: A Comparison between HCR-20 Version 2 and HCR-20 Version 3. Issue 2 (3rd April 2018) - Hopton, Jenny; Cree, Adrian; Thompson, Sean; Jones, Russell; Jones, Roland
ABSTRACT: In recent years more attention has been given to the crucial role of formulation when assessing and managing risk. There is evidence to suggest that not all clinicians are competent at producing formulations, despite this being a key competency. We investigated the quality of risk formulation in routine clinical practice in 121 forensic psychiatric hospital patients in the UK using the Case Formulation Quality Checklist Revised (CFQC-R). Next, we compared the quality of formulations in Version 2 and Version 3 of the HCR-20. The results overall showed that the quality was in the intermediate range, however, Version 3 formulations were of slightly better quality than Version 2. When formulations were considered in terms of word count, the findings suggested that longer formulations were not necessarily associated with higher quality. It appears that formulation quality has improved with the new version of the HCR-20, but there is a need for training in risk formulation for clinicians to improve the quality of those being produced.